Sistem Monitoring Suhu, Kelembaban dan Pengendalian Penyiraman Sayuran Hidroponik Menggunakan Bylink Android - Nelly Khairani Lestari; Davit Irawan; Richardo Afri Aldi (BEES: Bulletin of Electrical and Electronics Engineering, 2020)
Hydroponics is a method of farming that does not use soil as a planting medium, but only uses water that contains nutrients needed by plants. Meanwhile, hydroponic vegetables are horticultural commodities that are starting to be in great demand and being developed in the agricultural sector today. The specialty of hydroponic vegetables itself is that the quality produced is fresher, and cleaner than conventional vegetables. One of the success factors of planting with the hydroponic method is how to maintain and care for the grown vegetables so that they can be harvested with good results and not rot. Water circulation and nutrition must be carried out periodically and should not be excessive or deficient. However, if the plant owner is not there, the watering process and nutrition will be hampered. For this reason, a tool was designed to be able to help the process of watering, checking temperature and providing nutrition by combining the Arduino-uno's capabilities as a data acquisition system equipped with an ethernet shield for sending data via the internet network, DHT11 sensors to read temperature and humidity, special Android application Blynk as monitoring aids, and RTC for real time timing. The Arduino-Uno is also connected to a relay to regulate the ignition of the sprinkler pump or water circulator. Based on the tests conducted, it was found that each module can work properly according to its function. With the quality of the network according to the test (the average delay to the blynk server is 1242ms, the process of sending orders and executing water sprinkling and sending environmental data takes about 1-5 seconds.